PERBANDINGAN INDIKATOR KEUANGAN ANTARA BANK UMUM MILIK NEGARA DENGAN BANK UMUM SWASTA NASIONAL DI INDONESIA - Dian Lestari (Department of Development Economics, Universitas Sriwijaya, 2014)
Banks are crucial institutions for economy. Healthy banks can stabilize the economy. Bank Indonesia sets standars for a healthy bank: Capital, Assets Quality, Management, Earnings, Liquidity, and Sensitivity to Risk (CAMELS). This research is an attempt to identifity the healthiness status and different influence of variables such as CAR, NPL,ROA,ROE BOPO, and LDR on stste-owned and private banks in the period of 2003 to 2012 using CAMELS. The sample consists of four state-owned banks, that is, BNI, BRI, Bank Mandiri and BTN and four private banks, that is, BCA, Bank CIMB Niaga, Bank Danamon, and Bank Internasional Indonesia. The secondary data of these banks cover the period of 2003-2012. To analyze these data and prove the hypothesis of this research, Mann-Whitney, and Kolmogorov-Semirnov teste are used by the help of SPSS. The research results show that there exist different financial indicators used the two different groups of the banks as shown by NPL. The two test result in Asymp Sig < 0.05 meaning that NPL distinguishes the two groups. Other variables such as NPL, ROA, ROE, BOPO, and LDR do not indicate significant difference. Keywords: Financial Indicators, Public Banks, State-owned Comercial Banks, National Private Commercial Banks